FLOWER BIOLOGY OF TWO DIOSPYROS SPECIES NEIGHBORLY LIVE AT CSC AREA: DO POLLEN VIABILITY AND TUBE GROWTH RATE SHIRE ENDEMIC DISTRIBUTION - Erlin Rachman (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
Aims of study were to compare flower structure, pollen viability and pollen tube growth rate of two Diospyros species neighborly live in Cibinong Science Centre (CSC) park, Diospyros blancoi and D. celebica, and pursue if pollen-tube growth rate shire reasons endemic distribution of D.celebica in native habitat. Floral structurewas in situ or ex situ morphologically observed. Germination test and pollen tube growth incubation were done in Sarfatti medium and digitally captured and computerize analysis. The result showed that, both species have flower part resemblance each other. D. blancoi has bigger size in almost all flower parts. D. blancoi showed much more pollen viability (41% vs 7%) and tube growth rate than D. celebica1 (66 vs 0.57 μm per minute). Average pollen-tube length of both species at about 31/2 hours incubation was significantly different each other (342.679 ± 37.067 vs 128,673 ± 49,215μm). Most observed D. blancoi female trees set high number of fruit year to year and almost observed D. celebica female trees set very low number of fruit and some time without fruit in the year. It is associated with geographical distribution difference between the two species. Very significantlydifferent in pollen-germination percentage and pollen-tube growth rate provide a tool of further study to know microenvironment for reproduction and propagation of the endemic species, D. celebica.